1996
DOI: 10.3109/10428199609054788
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Hematological Characteristics of Hepatosplenic T γ/δ Lymphoma with Isochromosome for Long Arm of Chromosome 7

Abstract: Hepatosplenic T gamma/delta lymphoma is a rare entity of peripheral T cell lymphoma. Three of 386 patients with non-Hodgkin's lymphoma in our institute were found to have this subtype of lymphoma. All had chromosomal abnormalities of isochromosome 7q and trisomy 8. The clinical and hematological features of these three patients are reported. All were males with ages ranging from 23 to 29 years. Initial presentation comprised purpura and variable degree of hepatosplenomegaly. None had superficial lymphadenopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…Therefore, in the context of antigen-driven stimulation of reactive ␥␦ T cells, it is tempting to speculate that neoplastic transformation could result from a multistep process involving impairment of the immune system (as in the patients receiving immunosuppressive therapy) or additional genetic alterations such as isochromosome arm 7q. The latter aberration was present in 9 of 13 documented cases, further confirming the association between HS␥␦TCL and isochromosome arm 7q, which was reported as a hallmark not only of HS␥␦TCL 12,14,25,[28][29][30][31][32] but also of its unusual ␣␤ immunophenotypic variant. 33,35 Although the mechanism by which it might contribute to the pathogenesis of HSTCL is unknown, its previously reported accumulation in forms with features of cytologic progression suggests that it benefits the outgrowth of malignant clones.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, in the context of antigen-driven stimulation of reactive ␥␦ T cells, it is tempting to speculate that neoplastic transformation could result from a multistep process involving impairment of the immune system (as in the patients receiving immunosuppressive therapy) or additional genetic alterations such as isochromosome arm 7q. The latter aberration was present in 9 of 13 documented cases, further confirming the association between HS␥␦TCL and isochromosome arm 7q, which was reported as a hallmark not only of HS␥␦TCL 12,14,25,[28][29][30][31][32] but also of its unusual ␣␤ immunophenotypic variant. 33,35 Although the mechanism by which it might contribute to the pathogenesis of HSTCL is unknown, its previously reported accumulation in forms with features of cytologic progression suggests that it benefits the outgrowth of malignant clones.…”
Section: Discussionsupporting
confidence: 67%
“…The identification of this lymphoma subtype, recognized as a provisional entity in the Revised European American Lymphoma (REAL) classification, 26 has been further supported by its cytotoxic phenotype 11,27 and its strong association with the isochromosome arm 7q cytogenetic abnormality. 12,14,25,[28][29][30][31][32] More recently, a few cases of HSTCL with sinusoidal infiltration and an ␣␤ T-cell receptor phenotype have been reported. [33][34][35] This is now considered an immunophenotypic variant of the same disease entity in the World Health Organization (WHO) classification.…”
Section: Introductionmentioning
confidence: 99%
“…Rearrangements, translocations and other abnormalities in chromosome 7q have been detected in various tumor types and are particularly common in benign and malignant mesothelial tumors, secondary leukemias, testicular cancers and carcinomas of the ovary and prostate (31)(32)(33)(34)(35)(36). Furthermore, cardiovascular abnormalities occur in association with duplicated segments of chromosome 7 (37) or with terminal deletion of 7q (38).…”
Section: Discussionmentioning
confidence: 99%
“…The human CaT1 cDNA was obtained through a combination of low stringency screening, using 32 P-labeled rat CaT1 cDNA as a probe to screen a human small intestinal cDNA library (Clontech Laboratories, Inc., Palo Alto, CA) (1), and PCR amplification, using Marathon ready cDNA (Clontech). The resulting human CaT1 cDNA was sequenced bidirectionally.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies showed the presence of an isochromosome 7q, often associated with trisomy 8, 9,[13][14][15] inspiring the discussion that isochromosome 7q may represent the primary chromosomal aberration accompanied by trisomy 8 as a secondary change. 9 Meanwhile isochromosome 7q has been detected in 13 of the patients, all of them male, and associated with trisomy 8 in 10 cases, however, trisomy 8 without isochromosome 7 has not been reported (Table 4).…”
Section: Cytogeneticsmentioning
confidence: 99%